Functionalized cork-polymer composites (CPC) by reactive extrusion using suberin and lignin from cork as coupling agents - Fernandes, Emanuel M.; Aroso, Ivo M.; Mano, João F.; Covas, José A.; Reis, Rui L. (Composites Part B: Engineering, 2014)
High density polyethylene (HDPE) and cork powder were compounded in a co-rotating twin-screw extruder to obtain cork-polymer composites (CPC) with improved properties. Benzoyl peroxide (BPO) was used as initiator agent, and suberin or lignin isolated from cork enhanced filler-matrix bonding and promoted mechanical reinforcement with environmental benefits. The novel composites were characterized in terms of dimensional stability, evolution of morphology, thermal and mechanical properties and their performance was compared with that of composites containing polyethylene-grafted maleic anhydride (PE-g-MA) as coupling agent. As expected, composites with coupling agent present higher mechanical properties, lower water uptake and thickness swelling variation. Suberin acts as plasticizer with antioxidant benefits, while lignin works as a coupling agent, improving tensile modulus and maximum strength. Increasing lignin content does not improve the mechanical properties but improves thermal stability.
Keywords: Coupling agent; Electron microscopy; Extrusion; Fibre/matrix bond; Polymer-matrix composites (PMCs)

Hybrid cork–polymer composites containing sisal fibre: Morphology, effect of the fibre treatment on the mechanical properties and tensile failure prediction - Fernandes, Emanuel M.; Mano, João F.; Reis, Rui L. (Composite Structures, 2013)
In this study, we investigated the use of short sisal fibre with and without polyethylene-graft-maleic anhydride (PE-g-MA) as a strategy to reinforce cork–polymer composite (CPC) materials. The use of alkali treatment of sisal to improve fibre–matrix adhesion was evaluated. High density polyethylene (HDPE) was used as matrix and the composites were produced in a two-step process using twin-screw extruder followed by compression moulding. FTIR, TGA and XRD were used to confirm the sisal fibre modification. Additionally, morphology, density, diameter and tensile properties of the fibres were evaluated before processing. The hybrid composites containing cork powder (40 wt.%) and randomly distributed sisal fibres were evaluated in terms of morphology and mechanical properties. The use of a 10 wt.% sisal fibre in the presence of a 2 wt.% coupling agent based on maleic anhydride, has shown to improve the tensile and flexural properties of the composites. The higher mechanical properties were achieved by using alkali treated sisal fibres and PE-g-MA. In the presence of the coupling agent the composite morphology revealed good interfacial adhesion between the natural components and the polypropylene matrix, being in accordance with the mechanical results. Weibull cumulative distribution was successfully used to accurately predict the tensile strength failure of the hybrid CPC materials.
Keywords: Cork; Extrusion; Fibre reinforced plastic; Hybrid composites; Mechanical behaviour; Polymer–matrix composites (PMCs)